Reduction Of Co2 Emissions By Chemical Synthesis Processes In The Cement Industry - Juan Camilo Restrepo; Jorge Ivan Tóbon; Oscar Jaime Restrepo (The Minerals, Metals and Materials Society, 2016)
Portland cement is obtained by a conventional synthesis process from a mixture of limestone and clay at high temperature (1450 °C). This work reports the possibility to obtain cement silicates via alternative methods like Solution Combustion Synthesis (SCS), which optimize both time and temperature, and the consequences to energy efficiency and mitigation of CO2 emissions. The production of one ton of cement emits between 0.62 and 0.97 tons of CO2 into the atmosphere. In this process the CO2 emissions are between 21 and 59%. The combustion methods are chemical redox processes in which, at high temperature, a self-sustaining and fast wave is generated from using chemical precursors and organic fuels.